2021
DOI: 10.3390/ani11113088
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Analysis of Breed, Methodological, and Geographical Impact on Equine Sperm Progressive Motility

Abstract: Over the past five decades, there has been increasing evidence to indicate global declines in human semen quality. Parallel adverse trends measured in male animals indicate a potential environmental aetiology. This study evaluated the progressive motility (PM) of stallion ejaculate through a systematic review and meta-analysis. A total of 696 estimates of equine PM from 280 studies, which collected semen samples between the years 1990 and 2018, were collated for meta-analysis. The method of motility analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…(stallion* OR horse* OR equine* OR colt*) AND (sperm* OR (semen AND quality) OR insemin*) AND NOT (human* OR horseradish). Original articles retrieved from the implementation of the same search strategy for an alternative subset of databases (BASE, PubMed, PubAg) were included within the study (Perrett et al, 2021), following the same extensive review process reported within this review. The review considered all articles reporting data on fresh equine sperm progressive motility (PMOT) assessed objectively via…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…(stallion* OR horse* OR equine* OR colt*) AND (sperm* OR (semen AND quality) OR insemin*) AND NOT (human* OR horseradish). Original articles retrieved from the implementation of the same search strategy for an alternative subset of databases (BASE, PubMed, PubAg) were included within the study (Perrett et al, 2021), following the same extensive review process reported within this review. The review considered all articles reporting data on fresh equine sperm progressive motility (PMOT) assessed objectively via…”
Section: Systematic Reviewmentioning
confidence: 99%
“…The full texts for 68 articles were not available and unobtainable through library resources. An additional 76 articles were accepted through stage two screening from FC and BC searching and alternative databases (Perrett et al, 2021). During critical appraisal, 238 articles were excluded, resulting in 284 original articles (Figure 1) (Haddaway et al, 2017).…”
Section: Systematic Review Outputmentioning
confidence: 99%
“…EVJ is proud to have published BEVA Primary Care Clinical Guidelines on analgesia, 6 wound management 7 and pituitary pars intermedia dysfunction 8 . We are equally delighted to have published a small but growing group of systematic reviews, particularly in recent years, where high‐quality evidence is now available for equine anaesthesia, 9–11 PPID 12 and laminitis, 13,14 spinal disorders, 15 respiratory disorders, 16,17 lameness in working equids, 18 clinical predictive models, 19 vaccine efficacy, 20,21 sarcoid treatment, 12 use of furosemide, 22 reproduction, 23,24 physiotherapy, 25 diagnostic imaging 26 and on the prevalence of a range of infectious diseases 27–32 . Scoping reviews appraising the quality of existing evidence and identifying knowledge gaps exist for equine asthma, 33,34 colic, 35,36 synovial sepsis, 37 movement analysis, 38 rehabilitation, 39 wound management, 40 pregnancy loss, 41 laparoscopy for urogenital disorders 42 and end‐of‐life decision making 43 and EVJ is well represented amongst the journals that have published these evidence reviews.…”
mentioning
confidence: 99%
“…Perret et al [ 3 ] investigated the effect of breed, testing method, and geographic location on the progressive motility of horse sperm. Semen quality expressed as sperm motility in horses is an important indicator of suitability for reproduction and fertility.…”
mentioning
confidence: 99%